Final answer:
To prove the logical equivalence of (p → (q → r)) and (q → (p → r)), we can use a series of logical equivalences. By assuming the truth of both statements and applying conditional elimination and introduction, we can show that they are equivalent.
Step-by-step explanation:
To prove that (p → (q → r)) and (q → (p → r)) are logically equivalent, we can use a series of logical equivalences. Let's start:
- Assume p → (q → r) is true.
- Using conditional elimination, we get q → r.
- Assume q → (p → r) is true.
- Using conditional elimination, we get p → r.
- Now, let's prove (p → (q → r)) → (q → (p → r)).
- Assume p → (q → r) is true.
- Using conditional elimination, we get q → r.
- Using conditional introduction, assuming q is true, we can prove p → r.
- Using conditional introduction, we can prove (q → (p → r)).
- Therefore, (p → (q → r)) and (q → (p → r)) are logically equivalent.